Análise cinemática das articulações dos membros torácicos e pélvicos de ovinos hígidos - Faria, Luís Guilherme de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this study was to evaluate kinematic parameters of the forelimb and hind limbs in Santa Ines healthy sheep to create a database. In addition, the study analyzed the influence of age on kinematic values. Twenty-one clinically healthy entire female sheep will be divided into three groups: Group 1 – seven animals aged from 8 to 12 months, Group 2 - seven animals aged from 2 to 4 years, and Group 3 - seven animals aged above to 5 years. Before start data collection, the sheep were trained to be conducted to walking in a pre-determined space at constant velocity. A minimum of 5 valid trials were obtained from the right and left sides of each sheep. Data were analyzed by use of a motion-analysis program (Vicon Nexus). Flexion and extension joint angles, and angular velocity were determined for the shoulder, elbow, carpal, hip, stifle, and tarsal joints. Significant differences were observed in some kinematic parameters between groups: maximum angle (G1>G2), minimum angle (G1<G2, G2<G3), angular displacement (G1>G2, G2>G3, G1>G3), maximum angular velocity (G1>G2, G2>G3, G1>G3), minimum angular velocity (G1>G2, G1>G3) of the carpus; angular displacement (G1>G3, G2>G3), minimum angular velocity (G1>G3, G2>G3) of the shoulder; minimum angle (G1>G3, G2>G3), angular displacement (G1<G3, G2<G3) of the tarsus; minimum angle (G1>G3), maximum angular velocity (G1<G3, G2<G3) of the stifle; maximum angular velocity (G1>G2, G1>G3), minimum angular velocity (G1>G2) of the hip. Differences between groups were observed in the length of the forelimbs and hind limbs. In conclusion, some differences in kinematic variables may be considered age-related

O estudo foi realizado com o objetivo de avaliar parâmetros cinemáticos dos membros torácicos e pélvicos de ovinos da raça Santa Inês, para constituir um banco de dados normativos e de avaliar a hipótese da influência da idade nos valores cinemáticos. Para tanto, foram utilizados 21 ovinos hígidos, fêmeas, separados em três grupos assim constituídos: Grupo 1 – com 7 animais com idade entre 8 e 12 meses; Grupo 2 – com 7 animais com idade entre 2 a 4 anos de idade e Grupo 3 – com 7 animais adultos com idade acima de 5 anos. Antes da coleta dos dados, os animais foram cabresteados e treinados a se locomoverem em espaço pré-determinado. Para cada animal, foram escolhidas cinco trilhas para o lado direito e cinco para o lado esquerdo. Os dados foram analisados e regularizados pelo programa de análise de movimento Nexus (Vicon). Foram registrados os valores angulares e a velocidade angular das articulações do ombro, cotovelo, carpo, coxofemoral, joelho e do tarso. Comparando-se os grupos, foram observadas algumas diferenças, tais como ângulo máximo (G1>G2), ângulo mínimo (G1<G2, G2<G3), deslocamento angular (G1>G2, G2>G3, G1>G3), velocidade angular máxima (G1>G2, G2>G3, G1>G3) e velocidade angular mínima (G1>G2, G1>G3) do carpo; deslocamento angular (G1>G3, G2>G3) e velocidade mínima (G1>G3, G2>G3) do ombro; ângulo mínimo (G1>G3, G2>G3) e deslocamento angular (G1<G3, G2<G3) do tarso; ângulo mínimo (G1>G3) e velocidade máxima (G1<G3, G2<G3) do joelho; velocidade máxima (G1>G2, G1>G3) e velocidade mínima (G1>G2) da articulação coxofemoral. Ocorreram variações entre grupos nos comprimentos dos membros torácicos e dos membros pélvicos. Foi possível concluir que a idade influenciou as diferenças de alguns valores cinemáticos entre os grupos
Keywords: Ovino - Pesquisa; Cinematica; Locomoção animal; Pelve; Torax; Articulações - Pesquisa; Sheep